Service Delivery Management In E-Governance System With Special Reference To The Users Of Online Services (Journal of Namibian Studies : History Politics Culture, 2023)
India is the largest democratic country that is striving hard to move from developing status to developed country. Government is taking several initiatives to move in apositive direction. One among the initiatives is e-governance. According to Abdul Kalam e-governance is a strong tool for ensuring corruption free administration. E-governance helps to create SMART governance in the society (S=simple, M=Moral, A=Accountable=responsive and T=Transparent). In this regard the present study focus on identifying the demographic profile of the respondents, analyzing the effectiveness of e-governance initiatives from the view of users of e-services and finally to enquire about the problems experienced by the users of e-governance. For this a sample of 120 respondents are taken and data is collected through a structured questionnaire. Statistical tools like t-test, one way ANOVA and ranking methods are used for analyzing the data. It is found that employee attitude and performance is creating much disturbance in delivery of services as compared to infrastructure, information communication technology (ICT) perception and Government intervention. It is concluded that better service provider’s attitude and performance needs to be enlightened for better service delivery management in e-governance system.